Exploring the translational potential of PLGA nanoparticles for intra-articular rapamycin delivery in osteoarthritis therapy - Jian-Chao Ma; Tingting Luo; Binyang Feng; Zicheng Huang; Yiqing Zhang; Hanqing Huang; Xiao Yang; Jing Wen; Xiaochun Bai; Zhong-Kai Cui (Journal of Nanobiotechnology, 2023)
Abstract Osteoarthritis (OA) is a prevalent joint disease that affects all the tissues within the joint and currently lacks disease-modifying treatments in clinical practice. Despite the potential of rapamycin for OA disease alleviation, its clinical application is hindered by the challenge of achieving therapeutic concentrations, which necessitates multiple injections per week. To address this issue, rapamycin was loaded into poly(lactic-co-glycolic acid) nanoparticles (RNPs), which are nontoxic, have a high encapsulation efficiency and exhibit sustained release properties for OA treatment. The RNPs were found to promote chondrogenic differentiation of ATDC5 cells and prevent senescence caused by oxidative stress in primary mouse articular chondrocytes. Moreover, RNPs were capable to alleviate metabolism homeostatic imbalance of primary mouse articular chondrocytes in both monolayer and 3D cultures under inflammatory or oxidative stress. In the mouse destabilization of the medial meniscus (DMM) model, intra-articular injection of RNPs effectively mitigated joint cartilage destruction, osteophyte formation, chondrocytes hypertrophy, synovial inflammation, and pain. Our study demonstrates the feasibility of using RNPs as a potential clinically translational therapy to prevent the progression of post-traumatic OA. Graphical abstract